Spatio-temporal effects of projected climate on future crop suitability over West Africa - Egbebiyi, Temitope Samuel (Department of Environmental and Geographical Science, 2020)
Future climate is projected to deviate from present-day by unprecedented measure, hereafter climate departure, with direct consequences on food security. West Africa, one of the hotspots for climate departure globally, has suffered significantly from climate change impacts via extreme events with large impacts on food production. A better understanding of the impact of climate departure on crop growth suitability and planting season is still unknown and is highly needed in West Africa, owing to its high vulnerability and low adaptive capacity. This thesis developed a methodology aimed at defining the cropping system to investigate the projected timing of climate departures from historical variability and their impact on crop growth suitability over West Africa. For the study we used 4 statistically downscaled Global Climate Models, GCMs at station level for the period 1951- 2100 under RCP8.5 across the three AgroEcological Zones (AEZs) of West Africa for eight crops, cassava, maize, mango, orange, pearl millet, plantain, pineapple and tomato. Climate variables minimum mean monthly temperature and total monthly precipitation were used as input crop suitability model, Ecocrop to develop a new approach to define and characterise cropping systems departure from their normal regime, called crop-climate departure (CCD), to better understand the timing of future changes in crop suitability. Also, the concept of CCD was defined, tested and applied in West Africa for five different crops types, using 10 GCMs downscaled by regional climate model, RCA4 as input into crop suitability model Ecocrop. The downscaled GCMs were also employed to examine the impact at the different global warming levels, 1.5, 2.0 and 3.0oC on crop suitability over West Africa. Using the GCMs at station level, we develop the concept of crop-climate used in characterizing the suitability of different crop across the three AEZs of West Africa. The result highlights the constraint, a reduction in suitable area, of growing cassava and pineapple only in the Guinea zone by mid and end of century. In contrast, there is an observed and projected opportunity, increase in suitable areas, of growing maize in southern Sahel by the end of the century while mango remains suitable across the three West African AEZs. The application applying the concept crop-climate departure on different crop types showed in decrease suitable areas for most crops by the end of century with horticultural, cassava and cereals respectively are the crops mostly affected. The changes in crop-climate relationship suggests a future constraint in crop suitability could be detrimental to future food security over West Africa. Finally, our findings from the impact of different global warming levels, 1.5. 2.0 and 3.0oC highlights the potential of sustained suitability for all the crops and improved food security under 1.5oC global warming for all the six crops but a contrast under 3oC over West Africa except for cowpea and groundnut. Our findings for cowpea and groundnut showed an increase suitable area into the southern Sahel with increasing global warming level. The study holds great value at regional scale where improved preparedness and regional cohesion could make the difference in making decision for a food secure Africa. Further studies to explore associated short and long-term adaptation options to changes in crop-climate relationship are recommended.